2015
DOI: 10.1016/j.bjid.2015.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Microarray-based genotyping and detection of drug-resistant HBV mutations from 620 Chinese patients with chronic HBV infection

Abstract: The results of the current study revealed that the prevalence of nucleotide analogs (NA)-resistance in Chinese hospitalized HBV-positive patients was so low that intensive nucleotide analogs (NA)-resistance testing before nucleotide analog (NA) treatment might not be required. In addition, the present study suggests that chronic HBV patients with genotype C were infected with fitter viruses and had an increased prevalence of nucleotide analogs (NA)-resistance mutations compared to genotype B virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…A phylogenetic analysis performed using the PCR-product sequences indicated that 43.5% (20/46) of the patients were infected with HBV B genotype, 54.3% (25/46) with C genotype, and 2.2% (1/46) with D genotype (data not shown). Currently, the viral pathogenesis of HBV is considered to depend on the genotypes and not on geographic distributions [ 25 27 ]. HBV genotypes B and C are the major epidemic genotypes in China [ 28 ], and our study confirmed this.…”
Section: Resultsmentioning
confidence: 99%
“…A phylogenetic analysis performed using the PCR-product sequences indicated that 43.5% (20/46) of the patients were infected with HBV B genotype, 54.3% (25/46) with C genotype, and 2.2% (1/46) with D genotype (data not shown). Currently, the viral pathogenesis of HBV is considered to depend on the genotypes and not on geographic distributions [ 25 27 ]. HBV genotypes B and C are the major epidemic genotypes in China [ 28 ], and our study confirmed this.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the common substitutions, some unknown amino acid substitutions, such as rtD134N, rtL145M/S, rtF151Y/L, rtR153Q, rtS223A, rtI224V, and rtN248H, need to be further verified. In addition to viral quasispecies composition, many factors can affect treatment outcome, such as host immune status, baseline HBV DNA level and genotype [2022]. …”
Section: Discussionmentioning
confidence: 99%
“…DNA microarray was also utilized for high-throughput multiplex detection of gastrointestinal viruses [ 105 ], viruses transmitted by small mammals and arthropods [ 106 ], herpesviruses, enteroviruses and flaviviruses [ 107 ], HIV-1, HIV-2, and hepatitis viruses [ 108 ] and dual infection with two dengue virus serotypes [ 109 ] in human specimens. DNA microarray was used to identify and genotype drug-resistant mutations of HIV [ 110 , 111 ] to detect and genotype drug-resistant hepatitis B virus (HBV) mutations [ 112 ], to detect and genotype SARS coronavirus [ 113 ], and to detect and determine lineage of influenza B viruses [ 114 ]. During an outbreak of SARS in China in 2002, DNA microarray also served for the discovery of a new member of the coronavirus family [ 115 ].…”
Section: Molecular Diagnostic Techniques Of Medical Virusesmentioning
confidence: 99%